Global Multisector / Multicountry 3 - E Modelling: From COMPASS to GI FORS - Bernd Meyer; Christian Lutz; Marc Ingo Wolter (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2003)
The global dimension of environmental policy, which has become a subject of international policy with the concrete discussion of targets and instruments, constitutes a huge information gap for environmental policy. The authors postulate, that this can only be filled by the application of global economic environmental models, which have to meet certain requirements: A multisector and multicountry system with global coverage and bilateral trade linkage with econometrically estimated parameters is needed. The authors present the system COMPASS (Comprehensive Model of Policy Assessment) and the improved system GINFORS (Global Interindustry Forecasting System), which is just being constructed based on the experiences made with COMPASS. A discussion of the application of GINFORS in the EU project MOSUS (Modelling Opportunities and Limits for Restructuring Europe towards Sustainability) gives an impression of the power of the model to analyze global economic environmental questions and to forecast important environmental indicators.
Keywords: C23; 330; Global Modell; COMPASS; GINFORS; Multisector; Multicountry; environmental policy